Kualitas Pelayanan Kesehatan di Puskesmas Kecamatan Pagar Merbau Kabupaten Deli Serdang - Saragih, Aulia Yusuf; Suharyanto, Agung; Nasution, Chairika (Mahesa Research Center, 2025)
Health services are a form of public service that plays an important role in improving the quality of life of the community. This study aims to describe the quality of health services at the Pagar Merbau Health Center, Deli Serdang Regency, using a descriptive qualitative approach. The focus of the research is directed at the five dimensions of service quality according to the SERVQUAL model, namely, tangible (physical evidence), reliability (reliability), responsiveness (responsiveness, assurance (guarantee), and empathy (concern). The data collection technique was carried out through in-depth interviews, observations, and documentation of health center officers and the community using the service. The results of the study show that, in general, the quality of service is quite good, especially in the aspects of facility cleanliness, service accuracy, and the friendly attitude of officers. However, there are still several obstacles that affect the effectiveness of services, including a lack of patient understanding of procedures, suboptimal information delivery, and limited health personnel. These factors have an impact on several dimensions of service, especially responsiveness and assurance. This study recommends patient education, information strengthening, and human resource improvement to optimize services.